Karakter Fisikokimia Agar-Agar dari Rumput Laut Gracilaria sp. dengan Variasi Air Kelapa dan Lama Ekstraksi - Shandra Berliana; Noor Harini; Rista Anggriani (Food Technology and Halal Science Journal, 2020)
Agar is a complex polysaccharide hydrocolloid that can be obtained from seaweed from the family Gracilaria sp. The function of agar is for gelling agent, thickener, stabilizer. In this research the extraction of agar from seaweed Gracilaria sp. used coconut water is able to reduce sulfate in seaweed, so can improve the properties of gel flour agar. This research was conducted in two stages. The first stage uses a factorial randomized block design consisting of 2 factors with 3 repetitions. The first factor was the ratio of seaweed and the ratio of coconut water (1:25; 1:30; 1:35). The second factor was extraction time (60 minutes, 90 minutes, 120 minutes). The agar extraction results were analyzed for yield, moisture content, ash content, viscosity, and gel strength. The second stage of the study was the application of agar flour to tomato fruit leather used a Simple Randomized Design model with various concentration of agar (0.6%, 0.9%) compared to commercial agar (0.6%, 0.9%). The parameters analyzed were water content, thickness, tensile strength, pH, total dissolved solids, color intensity, and organoleptic (taste, appearance, elasticity, preference). The results showed that there was a significant influence on the ratio of seaweed and coconut water and the extraction time, the agar produced to yield, water content, ash content, viscosity, and gel strength. The best treatment of agar that based on the SNI approach was in the R3T3 treatment, (seaweed: coconut water ratio of 1:35 with extraction time of 120 minutes) with a yield of 32.27%, moisture content of 11.08%, ash content of 3.75%, strength gel 235.51gr / cm2, viscosity 24.09 cP. The second stage of the study, the best results was obtained by adding agar to 0.9% with a moisture content of 8.13%, total dissolved solids 23.79º Brix, pH 4.03, thickness 0.39 mm , tark strength 1.64 N /mm2, color intensity (L) 40.24, (a +) 22.92, (b +) 8.09, taste 5.9 (tasty), elasticity 5.65 (easy to roll), appearance 5,75 (interesting), like 5.4 (like).